Penilaian Risiko Semikuantitatif Logam Berat pada Ikan Salmon di Jabodetabek: Semi-Quantitative Risk Assessment of Heavy Metals in Salmon Distributed in Jabodetabek - Nindya Hambar Wasisto; Wini Trilaksani; Iriani Setyaningsih (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Salmon imports continue to rise, while there were indications in some waters of the salmon's origin country that is a potential danger of heavy metals contamination. This phenomenon raises awareness regarding the food safety of salmon consumption, therefore a risk assessment is crucial to be conducted. The purposes of this study were to determine the content of Hg, Pb, and Cd in salmon meat and to assess the risk of heavy metals in salmon consumption in Jabodetabek area. Salmon fish, 132 in total was randomly taken from Tanjung Priok Port, the heavy metal analysis used the Flameless Inductively Coupled Plasma Mass Spectrometry instrument, risk assessment based on the United States Environmental Protection Agency method and risk ranger based on Ross and Sumner, supported by systematic literature review and questionnaires. The heavy metals Hg, Pb, and Cd in salmon were detected at 0.0646±0.0056, 0.0505±0.0446, and 0.0119±0.0006 ppm, respectively, indicating that there were still below the thresholds set by Food and Drug Supervisory Agency of the Republic of Indonesia (0.5;0.2;and 0.1 ppm). The results of the semi-quantitative risk assessment for Hg, Pb, and Cd were 0.0567, 0.0013, and 0.0010 (less than 1) implying that salmon consumption have no a potential risk of hazard. However heavy metals are accumulated in human body, hence, the diet consumption analysis needed to be performed. The risk ranger showed that the estimated risk ranking of heavy metals was in the medium category. Based on the results, it can be concluded that imported and consumed salmon by Jabodetabek residents was still relatively safe.